EXTEND THE SHELF LIFE AND IMPROVING SENSORY PROPERTIES OF WHITE SOFT CHEESE BY ADDING CELERY …..LEAVES - & et al., awda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study  was aime to investigate the effect of addition different concentration of celery leaves  to white soft cheese ,Treated cheese between 2018-2019, ,The finely Celery (Apium graveolens)   leaves  were  adding  to crude white  cheese  after texturizing in three leveles  included (A,B,C)  in addition of control   antimicrobial activity of celery treated  cheese  against total account bacteria and coliform bacteria was estimated  during (0, 5, 10, 15, 20) days. The results were shown that the higher concentration of celery in treated cheese, had a lower concentration of  protein, lipid and ash content ( 16.81,15.13 and 4.30% respectively, but  it had a higher moisture content 59.50%.also the total bacteria  counts  were decreasing significantly (0.05 P)with accumulative of cheese during astorage periods, it was reached to 1.3x105 , 9.5x103, 9x103, 7.62x103 , 1.05x104     (cfu/g)  respectively comparing with control samples,the number of  coliform bacterial in celery treated cheese,  at  concentrations 15%  was achieved significant difference comparing with  other samples ( 8x103,10.2x104, 9.7x104 , 8.9x105, 9.5x107( log cfu/g )  respectively.